Correlation of preferences for social comparison goals and certain personality traits - E S Samoylenko (RUDN Journal of Psychology and Pedagogics, 2010)
The results of investigation of differences in preference of certain goals of social comparison in individuals with opposite personality traits evaluated with the Big Five test are presented.